Legal Protection for Victims of Sexual Violence in Indonesia in the Perspectives of Victimology and Fiqh Jinayah - Ariyanti, Vivi (Universitas Islam Negeri Profesor Kiai Haji Saifuddin Zuhri Purwokerto, 2023)
Sexual violence is a global problem that violates human rights and fundamental freedoms. This paper examines the laws and regulations that guarantee the protection of victims according to Indonesian laws and Islamic law. Regarding Indonesian laws, besides the basic rules in the form of the Act on the Crime of Sexual Violence, there are also ministerial regulations (Regulation of the Minister of Education and Culture, and Regulation of the Minister of Religion) that protect and guarantee the safety of everyone from sexual violence offences. This is the concern of higher education institutions, that they are on the right track to address the issue of sexual violence with more passion and precision. The issues of sexual violence have received greater attention in universities, so that intensive prevention and response efforts are very important, with the aim of combating sexual violence in universities, navigating the application of laws and regulations relating to sexual violence, and more broadly, fostering a culture of respect, inclusion and courtesy towards others. These national laws are in line with the Islamic precepts regarding protection of citizens in the maqasid al-shariah concept, in which sexual violence offences can fall into all three categories of jarimah: qisas, hudud, and ta'zir, depending on the type of crimes committed.